Tandem Mass Spectrometry for Structural Identification of Sesquiterpene Alkaloids from the Stems of Dendrobium nobile Using LC-QToF - Wang, Yan-Hong; Avula, Bharathi; Abe, Naohito; Wei, Feng; Wang, Mei; Ma, Shuang-Cheng; Ali, Zulfiqar; Elsohly, Mahmoud A.; Khan, Ikhlas A. (Planta Medica, 2016)
Dendrobium nobile is one of the fundamental herbs in traditional Chinese medicine. Sesquiterpene alkaloids are the main active components in this plant. Due to weak ultraviolet absorption and low content in D. nobile, these sesquiterpene alkaloids have not been extensively studied using chromatographic methods. Herein, tandem mass spectrometry combined with liquid chromatography separation provides a tool for the identification and characterization of the alkaloids from D. nobile. A total of nine sesquiterpene alkaloids were characterized by ultrahigh-performance liquid chromatography tandem mass spectrometry. These alkaloids can be classified into two subgroups that are represented by dendrobine and nobilonine. Tandem mass spectrometric studies revealed the fragmentation pathways of these two subgroup alkaloids that were used for the identification and characterization of other alkaloids in D. nobile. Characterization of these alkaloids using accurate mass and diagnostic fragments provided a reliable methodology for the analysis of D. nobile by ultrahigh-performance liquid chromatography tandem mass spectrometry. The limit of detection was defined as the signal-to-noise ratio equal to 3 : 1. Limits of detection of dendrobine and nobilonine were less than 30 ng/mL. The developed method was applied for the analysis of various Dendrobium species and related dietary supplements. Alkaloids were identified from D. nobile, but not detected from commercial samples including 13 other Dendrobium species and the 7 dietary supplements.
Keywords: Dendrobium nobile; Orchidaceae; shi hu; dendrobine; nobilonine; UHPLC-QToF/MS; tandem mass; sesquiterpene alkaloids